Vaginal Delivery Management of Hydrocephalic Fetuses in Wonosari Hospital : Case Report - Adzka Fahma Rodliya; Resa Paksi Mandariska (STIKes Ibnu Sina Ajibarang, 2023)
Fetal hydrocephalus is a congenital abnormality, which means the fetus is born with it, but babies and children can also experience it. Hydrocephalus pregnancy can trigger premature labor and can cause fetal distress. A 30 year old mother, G3P2A0, gestation age 34 weeks 4 days, was referred to Wonosari Hospital with diagnosis of Partus Prematurus Iminens (PPI), fetal hydrocephalus, and fetal distress. Based on the history of pregnancy examination at 24 weeks, the Biparietal Diameter (BPD) size of the fetal head was larger than the normal size, (5.94 cm), the fetus indicated ventriculomegaly, and on the third trimester ultrasound examination (32 weeks) the Biparietal Diameter (BPD) size is 9.49 cm so that the fetus is indicated for congenital hydrocephalus. The baby was born spontaneously, male, birth weight 2000 grams, body length 38 cm, head circumference 34 cm, chest circumference 24 cm, upper arm circumference 10 cm, born without crying, negative muscle tone, pale bluish skin color. From the results of this examination, it was confirmed that he was suffering from congenital hydrocephalus based on the physical appearance of the head, which was larger than the normal head size of premature babies in general, and dead..